The Paradox of Regulation and Reality: An Ethnographic Study of Inequality in Access to Fish Resources among Fishing Communities in Tanjung Luar, East Lombok - Murdi, Lalu; Myrtati Dyah Artaria; Sutinah (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
Research on fishing gear conflicts has been conducted extensively by experts, but conflicts related to space, policy, and the existence of awig-awig (local knowledge) have not received much attention. This study aims to analyse fishing gear conflicts caused by spatial exploitation, while also examining them from the perspective of government policy and the existence of local knowledge that regulates space in awig-awig, which is shared among fishermen. This study uses a qualitative approach with the Ethnohistory method. The research data comes from primary data in the form of interviews and observations as well as document reviews, while secondary data comes from articles, books, and other written documents. The data analysis techniques used are domain analysis, taxonomy, component analysis, and cultural theme analysis, with data validity reinforced using triangulation techniques. The results of the study show the following: 1) Historically, since the 1970s, there have been frequent conflicts between fishermen in Tanjung Luar, mainly caused by competition for fishing grounds between traditional and modern fishermen; 2) In Tanjung Luar, there are local customs and government policies that regulate fishing areas between traditional and modern fishermen, but in practice, modern fishermen have so far operated in small-scale fishing areas; 3) Conflicts over fishing gear in Tanjung Luar are due to the gap in access and income between small-scale and modern fishermen, both those who use Kerakat Mini and Rumpon.